Em busca do sentido: uma análise das estratégias de processamento textual em O milagre das folhas, de Clarice Lispector - Valente, Thiago Alves; Ferreira, Eliane Aparecida Galvão Ribeiro [UNESP] (My University, 2013)
This text aims to elucidate the textual processing strategies that give meaning to chronicle "The miracle of the leaves", of Clarice Lispector (1920-1977). Therefore, it starts from the basic postulate that the meaning is not in the fabric or verbal imagery, but the meanings constructed from the elements of language that are there to meet with the reader (BRONCKART, 2009, p. 257). Justified this reading strategy, since the chronic Lispector reveals multiple meanings endowed with a language and dialogue. The text processing is discussed in terms of an audience potentially youthful element that assigns characteristics relevant to the understanding of the functioning of this type of text in relation to younger readers. To achieve the goal, we start from the assumption that chronic, being a literary text endowed with aesthetic validity, not only conveys a content, but recreates it, adding to it new meanings.

Objetiva-se neste texto elucidar as estratégias de processamento textual que conferem sentido à crônica “O milagre das folhas”, de Clarice Lispector (1920-1977). Para tanto, parte-se do postulado básico de que o sentido não está na tessitura verbal ou imagética, mas nas significações construídas a partir dos elementos da linguagem que ali estão ao se encontrarem com o leitor (BRONCKART, 2009, p. 257). Justifica-se essa estratégia de análise, uma vez que a crônica de Lispector revela-se dotada de uma linguagem plurissignificativa e dialógica. O processamento textual será abordado no âmbito da enunciação e em função de um público potencialmente juvenil, elemento que atribui características relevantes para a compreensão sobre o funcionamento desse tipo de texto em relação a leitores mais jovens. Para a consecução do objetivo, parte-se do pressuposto de que a crônica, por ser um texto literário dotado de validade estética, não apenas veicula um conteúdo, mas recria-o, agregando-lhe novos sentidos.
In search of meaning: an analysis of the processing of textual strategies in the miracle of leaves by Clarice Lispector
Keywords: Text processing; Reading; Chronicle; Sense; Processamento textual; Leitura; Crônica; Sentido